Spory na temat roli budżetu ogólnego Unii Europejskiej w procesie integracji społeczno-gospodarczej - Stabryła, Katarzyna (Disputes about the Role of the European Union Budget in the Socio-Economic Integration, 2009)
The purpose of the article is to show the main arguments concerning the future of the European Union budget. During debates about the EU budget, two concepts are the most visible. The first opts for a growing role of the budget as the competences of the European Union will be widen. The second leans towards present structure of the budget without new functions and instruments. It seems that the present situation of the European economies confronted with the financial and economic crisis, is closer to the second option
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 316-323